Poverty and Income Distribution Analysis 2009 -2016 - Quispe Llanos, Renán (2017)
This research work intends to show two issues that are related and determine the social condition of a person or household, in addition to having an impact on the quality of life they will have: income and poverty. In effect, poverty is a condition of persons or households whose main characterization is the unsatisfaction of some need. On the other hand, the income related to the person or household is a resource that corresponds to all, as long as it has a source that generates it, and whose magnitude allows access to the satisfaction of human needs or the lack of access to satisfy them. An analysis of income, concentration indicators and determinants of income in the period 2009-2016 is also presented. From which a semi-logarithmic model is applied to quantify the dependence of income on the variables mentioned in a model.The study is oriented towards the analysis of poverty in the 2009-2016 period, from its construction, from the poverty and extreme poverty lines, as well as the incidences of poverty and extreme poverty. Unsatisfied basic needs are also studied and the integrated analysis of poverty is carried out. Finally, the components or factors that affect poverty are presented analytically, as a preamble to its modeling.